Infección Urinaria: Estudio Prospectivo del Valor Diagnóstico de Pruebas de Tamizaje en Niños Preescolares Hospitalizados - Huicho, Luis (1995)
A prospective study was performed in 108 hospitalized children younger than 2 years old from May 1994 to June 1995. Urine specimens obtained through suprapubic aspiration were assessed for nitrite, leukocyte esterase and leukocyturia. Quantitative urine culture was the reference test employed. Prevalence of urinary tract infection was 10% (11 of 108 patients). Sensitivity and negative predictive values were 100% for leukocyte esterase (cut-point criterion 10-25 leukocytes/ul) or for nitrite these same thresholds were used. For leukocyte esterase with positivity criterion of 500 leukocytes/ul, sensitivity and positive predictive values were 82% and 100%, respectively. Nitrite with threshold excluding slight color changes yield sensitivity of 91% and positive predictive value of 43%. Both specificity and negative predictive values remained high for either nitrite or leukocyte esterase with same cut-points. Leukocyturia showed a lower performance as compared with either nitrite or leukocyte esterase. Concordance for both nitrite and leukocyte esterase results strongly positive was 100%. Overall, 5 out 11 patients revealed urinary tract abnormalities as assessed by ultrasonography or micturating cystourethrography. Prompt antimicrobial therapy is recommended when an urine specimen obtained by suprapublic aspiration yields both nitrite and leukocyte esterase results strongly positive. In cases with either leukocyte esterase or nitrite positive, the decision will rest upon clinical judgement. In addition, ultrasonography and micturating cystourethrography should be performed systematically in all children younger than 2 years old with a definite diagnosis of urinary tract infection.